Training for MSME in Riang Gede Village, Tabanan, Bali in Developing Business Places Through Registration on Google Maps - Nuning Indah Pratiwi; Ariska Amanda Putri; Ketut Elly Sutrisni; Wahyu Indra Satria (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Rianggede Village is a village located in Penebel sub-district, Tabanan Regency, Bali, Indonesia. Micro, small and medium enterprises (UMKM) is a general term in the world of economics that refers to productive economic enterprises owned by individuals or business entities in accordance with the criteria stipulated by Law no. 20 of 2008. SME business actors have limitations in terms of capital because usually the capital owned is mostly focused on the production side. Then what about the promotion and sales side which of course also requires a lot of money? Here technology can play a role, one of which is Google My Business. One of the advantages of Google My Business is that it displays business profiles online and is already integrated with Google Maps and the Google search engine.